Prevalence and associations of central serous chorioretinopathy in elderly Chinese: the Beijing Eye Study 2011 - Li, Yang; Jonas, Jost B. (Acta ophthalmologica, 2016)
Purpose To determine the prevalence and associations of central serous chorioretinopathy (CSC) in elderly Chinese. Methods The population-based cross-sectional Beijing Eye Study 2011 included 3468 individuals (age: 64.6 ± 9.8 years; range: 50-93 years), who underwent enhanced depth imaging of spectral-domain optical coherence tomography (SD-OCT). CSC was defined as serous detachment of the retina in the macular region without signs of haemorrhages or signs of polypoidal choroidal vasculopathy, exudative age-related macular degeneration or other retinal vascular disorders, both on fundus photographs and on optical coherence tomography (OCT) images. Results Central serous chorioretinopathy was diagnosed in 10 eyes (prevalence rate: 0.15 ± 0.05%; 95% confidence interval (CI):0.06%, 0.25%) of 10 subjects (prevalence rate: 0.31 ± 0.10%; 95% CI: 0.12%, 0.50%). In five subjects, CSC was located foveally, and in five subjects, CSC was located extrafoveally. All subjects affected by foveal CSC were men, and three of the five individuals with extrafoveal CSC were men. In univariate analysis, subjects with CSC were significantly younger than the remaining study participants, and foveal CSC showed a significant (p = 0.02) predilection for men. After adjusting for age and gender, individuals with foveal CSC (383 ± 112 μm versus 270 ± 47 μm; p = 0.02) and the whole group of subjects with CSC had a significantly thicker subfoveal choroid. In a parallel manner, eyes contralateral to eyes with foveal CSC showed a significantly thicker subfoveal choroid than the age-adjusted control group (413 ± 74 μm versus 270 ± 47 μm; p = 0.001). Conclusions In Chinese aged 50+ years, the prevalence of CSC was 0.14% per subject. The choroid in the CSC affected eyes and in the contralateral unaffected eyes was significantly thicker than in an age- and gender-adjusted control population-based group.
Gesehen am 24.06.2019